Non-Uptake of Newborn Screening in Planned Homebirth Is Associated with Preventive Health Practices for Infants: A Retrospective Case-Control Study - Chen Stein-Zamir; Hanna Shoob; Sandra Katan; Gina Verbov; Shlomo Almashanu (International Journal of Neonatal Screening)
Universal Newborn Screening (NBS) programs (for endocrine, immunologic and metabolic disorders) are effective in reducing child morbidity and mortality. Despite available health services, NBS is not carried out for some newborns. The contributing factors for this should be explored. In high-income settings, homebirth generally refers to planned birth at home, attended by skilled health professionals. We aimed to assess trends and characteristics of planned homebirths and the uptake of NBS and infant health practices. A retrospective case-control study including 3246 infants compared planned homebirth (cases) to age-matched hospital birth controls. During 2016–2023, 0.56% of livebirths (1623/290,458) in the Jerusalem District (JD), Israel, were planned homebirths. The rate has increased since 2020 (COVID-19 pandemic), 0.45% in 2016–2019 vs. 0.67% in 2020–2023. Homebirth infants had a higher birthweight, lower firstborn rate and higher socioeconomic rank. The overall NBS uptake in homebirths was significantly lower (73.7% vs. 99.5% in hospital births) and declined over time (81.1% in 2016–2019 vs. 68.7% in 2020–2023). Regarding preventive health practices for homebirth infants, the registration rate to Mother and Child Health Clinics (MCHCs) was lower (47.1% vs. 92.8% in hospital births), and routine immunization rates were decreased (DTaP-IPV-HiB3 90.7% vs. 60.1%). The NBS uptake among homebirth infants was significantly associated with MCHC registration and routine immunizations (RR = 4.15, 95%CI 3.3–5.3). NBS uptake in homebirths is considerably lower and is associated with subsequent patterns of preventive health practices. Notably, the national NBS program data also indicate a trend of increase in non-uptake rates. Barriers to NBS for homebirths should be identified and targeted interventions implemented. The trends in national NBS non-uptake necessitate further follow-up, and evidence from successful outreach programs should be reviewed and translated into guidelines for health organizations.